Strategi Pemerintah Dalam Pengembangan Sumber Daya manusia Di Wilayah Perbatasan - Hesty Tambajong; Samel W Ririhena; Hubertus Oja; Paul A Moento (Universitas Musamus, Merauke, Papua, 2024)
South Papua Province is one of the youngest provinces and also a province that borders another country, namely Papua New Guinea. The formation of the South Papua province in the context of development so that each region is able to cultivate the potential that exists in that region. Potential development starts with the development of human resources, starting from small communities, namely village communities. This research aims to analyze the government's strategy in developing human resources, especially in villages located in border areas, namely Sota District and Ninati District. The research uses qualitative research methods with literature studies and border village development data. The analytical methods used generally include qualitative descriptive analysis using analysis from Miles and Huberman in the form of interactive analysis. The results of this research indicate that the government's strategy for developing human resources in the education sector is to improve the quality of education and increase educational assistance quotas in various ministries specifically for Papuan students as well as building school building infrastructure and the availability of teaching staff. Training and Development for the community and state apparatus by providing training and guidance to improve skills and knowledge. Economy and Health, the government provides business capital to improve welfare and provides health equipment and health personnel to improve the quality of public health